Kajian Gallery di Jawa Tengah Dengan Langgam Arsitektur Neo Vernakular - Villa Della Rose; Heru Subiyantoro (Universitas Pahlawan Tuanku Tambusai, 2023)
Semarang Contemporary Art Gallery is located in the city of Semarang. It started with being the Pastor's house and turned into several different buildings until it finally became the Contemporary Art Gallery building. This gallery building is located on the side of the city which has a high historical value so that visitors can feel the history that has happened in it. Neo Vernacular architecture is architecture that applies exist architectural elements both physically and non-physically with the aim of preserving local elements that exist in a place which then undergoes renewal towards becoming a more advanced or modern work without forgetting local traditional values. in this case the author uses a descriptive research method approach in order to find out more about the object Gallery.